A Randomized Field Experiment Using Self-Reflection on School Behavior to Help Students in Secondary School Reach Their Performance Potential - Feron, Eva; Schils, Trudie (Frontiers in Psychology, 2020)
Recent policy reports documented that a growing group of students in secondary education could perform better given their expected performance. Studies showed that school performance is related to a range of social-emotional factors, including self-awareness, self-management, social awareness and responsible decision making. However, experimental studies in schools on the relation between these factors and school performance are scarce and results are mixed. This study used a randomized field experiment to examine whether self-reflection on school behavior of underperforming secondary school students affected their school performance (GPA), school engagement and self-concept. The sample comprised 337 9th grade students (M = 15.74 years old; SD = 0.58) from 18 secondary schools in the Netherlands. The intervention was designed in co-creation with teachers, to be as close to school practice as possible. Underperformance was measured using achievement test scores from both primary and secondary school, supplemented with teacher and parental assessments. Different model specifications were estimated to perform the analyses, and test for robustness of findings. The results showed that for treatment compliance, students with higher school motivation were approximately 29 percent more likely to comply. Students who reported higher levels of self-concept of school tasks were 17 percent less likely to comply. No significant effects of the treatment were observed on students’ GPA, school motivation, hours spent on homework or self-concept of school tasks. The treatment showed a negative effect on self-concept of leadership skills.